Comprehensive utilization of edible mushroom Auricularia auricula waste residue—Extraction, physicochemical properties of melanin and its antioxidant activity. Issue 11 (21st October 2019) - Liu, Xin; Hou, Ruolin; Wang, Danting; Mai, Mengxian; Wu, Xiaoping; Zheng, Mingfeng; Fu, Junsheng
Abstract: In order to promote the comprehensive utilization of the Auricularia auricula waste residue, the extraction process and the physicochemical properties of melanin from A. auricula waste residue were studied. Furthermore, the chemical antioxidant activity of waste residue melanin and its protective effect on cell oxidative injury induced by H2 O2 were investigated. The results indicated that the ultrasonic‐assisted extraction process could be used to extract the melanin from A. auricula waste residue. Melanin had a good solubility in alkali solution and exhibited a certain stability to thermal. There was no significant difference between A. auricula melanin control group and waste residue melanin on ABTS, DPPH, and hydroxyl radical scavenging activity. Waste residue melanin significantly inhibited the cell death caused by H2 O2, and the cell viability was restored to 98.09 ± 5.97% when the melanin concentration was 1.6 mg/ml. Cell morphology observation confirmed that the melanin ameliorated the morphological changes of cells induced by oxidative stress. Abstract : Melanin, one of the main components of Auricularia auricula, still remains in the waste residues of A. auricula fruit body after extracting polysaccharides and other active substances. In order to promote the comprehensive utilization of the A. auricula waste residue, we studied the extraction technology, physicochemical properties of melanin from the waste residue of A. auricula, and its protective effect on oxidative damage of cells. The results showed that the ultrasonic‐assisted extraction process could improve the extraction rate of melanin from A. auricula waste residue; the residue melanin had good antioxidant activity and could protect cells from oxidative stress damage.